2011
DOI: 10.3389/fnsys.2011.00038
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Specificity in Basal Ganglia Related Movement Disorders

Abstract: The basal ganglia (BG) are a group of interconnected nuclei which play a pivotal part in limbic, associative, and motor functions. This role is mirrored by the wide range of motor and behavioral abnormalities directly resulting from dysfunction of the BG. Studies of normal behavior have found that BG neurons tend to phasically modulate their activity in relation to different behavioral events. In the normal BG, this modulation is highly specific, with each neuron related only to a small subset of behavioral ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 150 publications
3
28
0
Order By: Relevance
“…For example, dystonia shares many physiologic features with PD. Both disorders exhibit enhanced neuronal oscillations, synchrony, and burst-firing in the STN[124]andGPi[105,125127]. Thus,noneofthese changes in and of themselves can drive parkinsonism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, dystonia shares many physiologic features with PD. Both disorders exhibit enhanced neuronal oscillations, synchrony, and burst-firing in the STN[124]andGPi[105,125127]. Thus,noneofthese changes in and of themselves can drive parkinsonism.…”
Section: Discussionmentioning
confidence: 99%
“…Related to synchrony is the loss of specificity of BG neurons for passive and active movement [105]. The proportion of neurons with firing rate changes during movement is larger in MPTP treated monkeys compared to controls [106], and an increased proportion of BG and thalamic neurons encode for movement about multiple joints [62, 107].…”
Section: Electrophysiological Changes In Animal Models Of Pdmentioning
confidence: 99%
“…22 There is evidence to suggest that basal ganglia dysfunction in PD leads to a loss of specificity of surviving neurons and their connected structures. 23 Such changes could alter the precise coupling between sensory inputs and motor outputs that is characteristic of motor cortex. Since PAS relies on the interaction between sensory afferents and motor out- Abbreviations: ADM ϭ abductor digiti minimi; APB ϭ abductor pollicis brevis; PAS ϭ paired associative stimulation.…”
Section: Resultsmentioning
confidence: 99%
“…Focal microinjections of the GABA-A antagonist bicuculline in the striatum lead to loss of specificity (LOS) in BG firing patterns (Bronfeld and Bar-Gad, 2011) and cause repetitive motor tics confined to a single or a few muscles (McCairn et al, 2009). Bronfeld and Bar-Gad (2011) showed that LOS actually is a general phenomenon in BG movement disorders, including PD.…”
Section: Introductionmentioning
confidence: 99%
“…Bronfeld and Bar-Gad (2011) showed that LOS actually is a general phenomenon in BG movement disorders, including PD. The activity of the projection neurons (∼95%) in the striatum, the medium spiny neuron (MSN), is controlled by, e.g., recurrent inhibition and feed-forward inhibition from fast spiking neurons (FSNs).…”
Section: Introductionmentioning
confidence: 99%